THE CONSTITUTION OF THE SISTERS OF CHARITY: A DOCUMENT OF THE ENFLESHED SPIRIT - Purba, Mida (LOGOS, 2013)
We are going to examining Vincentian spiritual heritage of the Congregation of the Sisters of Charity (SC) in North Sumatra, as enshrined in the words of their Constitution. It will become clear that spiritualities expressed in the words of documents are enfleshed spiritualities: moulded, influenced, and shaped by concrete and particular human historical situations. This section begins with a brief account of the sequential development of the SC Constitution. A thorough discussion and subsequent analysis will focus on the latest version of the foundational document published in 2003. A concluding section will close this examination. Â